1984
DOI: 10.1037/0022-006x.52.2.315
|View full text |Cite
|
Sign up to set email alerts
|

A note on the congruence of the WISC-R and the cognitive development scales of the Personality Inventory for Children.

Abstract: This research assessed the criterion validity of three cognitive development scales within the Personality Inventory for Children via correlations with the Wechsler Intelligence Scale for Children-Revised (WISC-R). Results suggest that the Inventory has validity for the task of screening children's cognitive abilities. One unexpected finding suggests that the WISC-R freedom from distractibility factor may reflect sensitivity to internal rather than external stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
10
1
Order By: Relevance
“…However, a high correlation (−.67) between the Somatic Concern scale of the PIC and the Third Factor was also obtained by Dollinger et al (1984). This scale reflects the presence of health-related problems, such as frequent somatic complaints, poor appetite, sleep difficulties, and low energy level, that may be associated with a real physical problem, stress, depression, anxiety, or avoidance of responsibilities.…”
Section: Third Factor and Measures Of Personality/emotional Disturbancementioning
confidence: 97%
See 2 more Smart Citations
“…However, a high correlation (−.67) between the Somatic Concern scale of the PIC and the Third Factor was also obtained by Dollinger et al (1984). This scale reflects the presence of health-related problems, such as frequent somatic complaints, poor appetite, sleep difficulties, and low energy level, that may be associated with a real physical problem, stress, depression, anxiety, or avoidance of responsibilities.…”
Section: Third Factor and Measures Of Personality/emotional Disturbancementioning
confidence: 97%
“…Furthermore, lower Third Factor scores for the hyperactive group supports the traditional "Freedom From Distractibility" interpretation of the Third Factor because distractibility is a key component of hyperactivity (American Psychiatric Association, 1987;Kerasotes& Walker, 1983). Dollinger, Goh, and Cody (1984) and Beck and Spruill (1987) correlated the scales of the Personality Inventory for Children (PIC; Wirt, Lachar, Klinedinst, & Seat, 1979) with Full Scale, Verbal, Performance, and Third Factor IQ scores on the wisc-R. A significant correlation between the Third Factor and the Development scale of the PIC was the only correlation to replicate across both studies. Elevations of the PIC Development Scale are associated with distractibility, poor study skills, deficits in fine and gross motor skills, delayed intellectual development, language problems, delays reaching developmental milestones, and speech difficulties (Lachar & Gdowski, 1979).…”
Section: Third Factor and Measures Of Personality/emotional Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…Bennett and Welsh (1981) reported ACH scale scores to be more highly correlated than IS scale scores with IQ and Achievement scores. Dollinger et al (1984) found that the cognitive triad of the PIC correlated highly with Wechsler Intelligence Scale for Children-Revised between the other PIC clinical scales and the WISC-R, predicting that the Hyperactivity (HPR) scale of the PIC would correlate significantly with the WISC-R Freedom From Distractibility (FD) factor. Contrary to their expectations, the HPR scale did not correlate with the FD factor; instead, the FD factor was significantly correlated with the Somatic Concern (SOM) scale of the PIC, leading them to hypothesize that the FD factor may reflect sensitivity to internal rather than to external stimulation.…”
mentioning
confidence: 99%
“…Finally, the research literature about the validity of the PIC in school assessments is relatively large, which we briefly summarize here. Scores from PIC scales constructed as measures of child cognitive–scholastic functioning (e.g., Achievement, Intellectual Screening, and Development) correlate about −.60 to −.40 with scores from individually administered IQ and achievement tests for preschool and elementary-school children (e.g., Bennett & Walsh, 1981; Byrne, Backman, Gates, & Clark-Touesnard, 1986; Byrne, Smith, & Backman, 1987; DeMoor-Peal & Handal, 1983; Dollinger, Goh, & Cody, 1984; Handal & DeMoor-Peal, 1985; Keenan & Lachar, 1988), although some researchers have reported somewhat lower correlations (−.40 to −.30 within a clinic-referred school-age sample; Beck & Spruill, 1987). (High scores on PIC scales indicate greater problems; thus, these correlations are negative.)…”
mentioning
confidence: 99%